Associations between fluorescence optical imaging and magnetic resonance imaging and symptoms in hand osteoarthritis. (30th January 2021) - Maugesten, Øystein; Ohrndorf, Sarah; Slatkowsky-Christensen, Barbara; Kvien, Tore K; Uhlig, Till; Haugen, Ida Kristin
Abstract: Objectives: To investigate whether Fluorescence Optical Imaging (FOI) enhancement and MRI-defined synovitis are associated with pain and physical function in hand OA patients. Methods: Bilateral FOI scans and MRI of the dominant hand were available for 221 patients. Finger joints were examined for tenderness on palpation. Pain in individual finger joints during the last 24 h and last 6 weeks and hand pain intensity by the Australian/Canadian hand index and Numeric Rating Scale were self-reported. On joint level, we applied logistic regression with generalized estimating equations to examine whether FOI enhancement and MRI-defined synovitis were associated with pain in the same joint. On subject level, we applied linear regression to assess whether FOI and MRI sum scores were associated with pain intensity and physical function. Results: Metacarpophalangeal and thumb base joints were excluded from analyses due to little/no FOI enhancement. Finger joints with FOI enhancement on the composite image had higher odds (95% CI) of pain during the last 6 weeks [grade 1: 1.4 (1.2–1.6); grade 2–3: 2.1 (1.7–2.6)]. Similar results were found for joint pain during the last 24 h and joint tenderness in fingers. Numerically stronger associations were found between MRI-defined synovitis and finger joint pain/tenderness. FOI and MRI sum scores demonstrated no/weak associations with hand pain and physical function. Conclusion: FOI enhancement and MRI-defined synovitis were associated with pain in the same finger joint. None of the imaging modalities demonstrated consistent associations with pain, stiffness and physical function on subject level.